Pengaruh Pembelajaran Berdiferensiasi Berbasis Permainan Terhadap Motivasi Dan Hasil Belajar Pendidikan Jasmani Siswa Sekolah Dasar Negeri 10 Linge - Alyadi S; Dedy Syahputra; Syah Iskandar; Muhammad Fathir; Furkan; Sri Wahyuni (CV. Abid Abadi Jaya, 2026)
This study aimed to examine the effect of differentiated game-based learning on the motivation and learning outcomes of fourth-grade students in physical education at SD Negeri 10 Linge. The study employed a quantitative approach using a quasi-experimental method with a One-Group Pretest–Posttest Design. The participants consisted of 28 fourth-grade students selected through a total sampling technique. The research instruments included a learning motivation questionnaire and a physical education performance test, both of which were validated and tested for reliability before implementation. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, Levene’s homogeneity test, and the Paired Sample t-test with the assistance of SPSS version 21 at a significance level of 0.05. The findings revealed that the mean motivation score increased from 16.18 in the pretest to 20.46 in the posttest, while the mean learning outcome score improved from 69.14 to 84.39. The paired sample t-test indicated a significance value of 0.000 (p < 0.05) for both variables, demonstrating a statistically significant improvement following the implementation of differentiated game-based learning. These findings suggest that differentiated game-based learning is an effective instructional strategy for enhancing students' learning motivation and physical education achievement by accommodating diverse learning needs and encouraging active participation in the learning process.